The predictive roles of character strengths and personality traits on flourishing - EKŞİ, HALİL (My University, 2022)
This research aims to explore the association between personality traits, character strength, and flourishing in university students (N=384). In the study, Three-dimensional Character Strengths Scale was adapted to Turkish. As a result of confirmatory factor analysis, the Three-dimensional Character Strengths Scale was acceptable for the goodness of fit indexes. The results of the study showed that personality traits and character strength were positively related to flourishing. Multiple regression analysis revealed that personality traits, with the exception of the openness, significantly predicted flourishing. According to the standardized beta coefficients, extraversion was found to be the strongest predictor of flourishing. According to the results of multi-regression analysis, it was found that the caring, inquisitiveness and self-control sub-dimensions of the character strengths positively predicted the flourishing. According to the standardized beta coefficients, inquisitiveness was found to be the strongest predictor of flourishing. According to the t test results, it was found that the variables included in the study differed significantly according to gender. The findings were discussed with the literature.
Keywords: Personality traits; character strengths; psychological well-being; flourishing; positive psychology